PENGHASILAN TIDAK KENA PAJAK (PTKP) SEBAGAI BENTUK PERLINDUNGAN HAK EKONOMI DALAM PERSPEKTIF HAK ASASI MANUSIA - Saputra, Auditya Firza (UI Scholars Hub, 2021)
As a ratifying State to the International Covenant on Economic, Social and Cultural Rights (Ecosoc), the Government of Republic of Indonesia has legal obligation to implement steps of realization in effective and measurable manner in fulfilling, promoting, and protecting the economic, social and cultural rights of all its citizens. The issue is, to fulfil such obligation the State will require high amount of cost. The State is being sourced by the taxation policy. From many taxation policies, Income Tax become one of the most preffered segment. Unfortunately, the Income Tax policy, in practice, hardly optimizing due to many social economic issues on society, such as the high level of poverty, welfare issues, and the existing under minimum wage issues among the workers. These issues eventually affect societys purchasing power towards minimum level, and inconsequently making tax absorbtion unoptimal. The Government issued Non Taxable Income Tax Law policy to protect the buying power of those under welfare level to improve its own economic situation. Such protection will be reviewed in this article through Human Rights perspective using interdisciplinary point of view, including law, sociology, and economy.